Geochemistry of shield stage basalts from Baluran volcano, East Java, Sunda arc - Esti Handini; Toshiaki Hasenaka; Nicholas D Barber; Tomoyuki Shibata; Yasushi Mori (Journal of Applied Geology, 2022)
We report petrography and geochemistry of basaltic lava flows from the shield stage of Baluran, a Quaternary volcanic center in the rear of East Java, Sunda Arc, Indonesia. These basalts contain abundant plagioclase, clinopyroxene, olivine, and minor magnetite. Geochemically, they resemble other medium-K calc alkaline basalts from eastern Java’s volcanoes, but they are less enriched in light ion lithophile elements (LILE) and Pb. The predicted primary basalt of Baluran lavas can be sourced to a more primitive primary melt composition which may also generate medium-K calc-alkaline magmas in the region. The fractionation trajectory of these primary magmas shows the importance of plagioclase, clinopyroxene, olivine, and magnetite phase removal from the melt. Regardless of the diverse composition of the derivatives, the calculated primary basalts from the eastern Java are all in the field of nepheline-normative. This finding suggests variably small degree of melting of clinopyroxene-rich mantle source is at play in the generation of these magmas. Our result further suggests that the clinopyroxene source rock is possibly present as veins in peridotite mantle which have experienced metasomatism by addition of slab-derived fluids at differing proportion.